Sinergitas Dinas Sosial dan Panti Sosial Tresna Werdha Wana Seraya dalam Penanganan Lanjut Usia Terlantar di Kota Denpasar - Larasati Winanda, Ni Kadek Markis Ari; Winaya, I Ketut; Supriliyani, Ni Wayan (CITIZEN CHARTER, 2021)
Denpasar city is currently working on getting neglected elderly people to get better and maximum protection as they should be as parents who must be respected. This study aims to determine how synergy in Social Service of Denpasar City Social Service of Bali Province and Tresna Werdha Wana Seraya Social Institution in the handling of neglected elderly people in Denpasar City. Researchers used descriptive qualitative research methods with data collection techniques interview, observation and documentation. The results of this study use two indicators of synergy according to Najiyati, namely communication and coordination, which shows that the synergy that exists midst Social Service of Denpasar City Social Service of Bali Province and Tresna Werdha Wana Seraya Social Institution has been running well. But there are still some shortcomings that must be improved so that in the future more optimal synergy. Keywords : Synergy, Abandoned Elderly, Elderly Welfare.